Organizational Cynicism Reviewed from Work Stress to Shipping Employee Organization Support - Putrie, Hesa Chikita; Faraz, Faraz (Psikostudia : Jurnal Psikologi, 2022)
The study aimed to determine the role of work stress and the perception of organizational support for organizational cynicism in shipping employees. The study used a quantitative approach with 152 respondents. The research instrument uses the organizational cynicism scale of Yunida, (2016), the work stress scale of Sari et al. (2018), and the survey scale of perceived organizational support from Kurtessis et al. (2017). Data retrieval is done online, then the data that has been collected, analyzed with multiple linear regression tests using SPSS software. The results showed that the significance value p = 0.00 (p < 0.05) so it can be said that work stress and perception of organizational support influence the organization's cynicism in shipping employees in the era of the COVID-19 pandemic. Work stress had an effective contribution of 31%, while effective contributions perceptions of organizational support were greater at 32%. Based on these results, it is very important to pay attention to organizational support for employees to avoid the emergence of organizational cynicism. Penelitian ini bertujuan untuk menentukan peran stres kerja dan persepsi dukungan organisasi untuk sinisme organisasi dalam karyawan pengiriman. Penelitian ini menggunakan pendekatan kuantitatif dengan 152 responden. Instrumen penelitian menggunakan skala sinisme organisasi Yunida, (2016), skala stres kerja Sari et al. (2018), dan skala survei dukungan organisasi yang dirasakan dari Kurtessis et al. (2017). Pengambilan data dilakukan secara online, kemudian data yang telah dikumpulkan, dianalisis dengan tes regresi linier berganda menggunakan perangkat lunak SPSS. Hasil penelitian menunjukkan bahwa nilai signifikansi p = 0,00 (p < 0,05) sehingga dapat dikatakan bahwa stres kerja dan persepsi dukungan organisasi mempengaruhi sinisme organisasi dalam mengirimkan karyawan di era pandemi COVID-19. Stres kerja memiliki kontribusi efektif sebesar 31%, sementara persepsi kontribusi yang efektif tentang dukungan organisasi lebih besar pada 32%. Berdasarkan hasil ini, sangat penting untuk memperhatikan dukungan organisasi bagi karyawan untuk menghindari munculnya sinisme organisasi.